2017
DOI: 10.1093/bja/aex004
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary aspiration during procedural sedation: a comprehensive systematic review

Abstract: This first systematic review of pulmonary aspiration during procedural sedation identified few occurrences outside of gastrointestinal endoscopy, with full recovery typical. Although diligent caution remains warranted, our data indicate that aspiration during procedural sedation appears rare, idiosyncratic, and typically benign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 86 publications
0
90
0
2
Order By: Relevance
“…The limitations of contrasting such estimates must again be recognised, as they include aggregate patients without factoring in the presence or absence of specific aspiration risk factors (discussed in Question 2). Only 34 occurrences of non‐endoscopic sedation‐associated aspiration have been reported in the medical literature from 1985 to 2016, affirming the rarity of this event. As noted earlier, reasonable point estimates for aspiration mortality associated with general anaesthesia are 1:78,732 for adults and immeasurably small for children.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The limitations of contrasting such estimates must again be recognised, as they include aggregate patients without factoring in the presence or absence of specific aspiration risk factors (discussed in Question 2). Only 34 occurrences of non‐endoscopic sedation‐associated aspiration have been reported in the medical literature from 1985 to 2016, affirming the rarity of this event. As noted earlier, reasonable point estimates for aspiration mortality associated with general anaesthesia are 1:78,732 for adults and immeasurably small for children.…”
Section: Resultsmentioning
confidence: 97%
“…A recent systematic review of the literature identified 35 papers describing one or more occurrences of procedural sedation‐associated aspiration between 1985 and 2016 . These reports included 292 occurrences of aspiration during gastro‐intestinal upper endoscopy, with eight deaths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of anesthesia reported was longer (45‐115 minutes), compared to the time it typically takes to complete botulinum toxin injections, which is likely an important difference. In addition, medications given to provide anxiolysis can cause respiratory depression and increase the risk of aspiration . Although general anesthesia and conscious sedation as well as medication for anxiolysis come with risks, there are also risks to completing the procedure without any medications for comfort.…”
Section: Discussionmentioning
confidence: 99%
“…While aspiration of gastric contents is a theoretical risk,9 this position also provides some protection; additionally patients are routinely fasted and the endoscopist is able to remove residual gastric contents by suction. In practice, aspiration pneumonia is very rare in endoscopy27 and can also occur with tracheal intubation 18. In addition, general anaesthesia considerably prolongs the procedure1 and exposes the patient to the well-known hazards of direct laryngoscopy 28 29.…”
Section: Discussionmentioning
confidence: 99%